Qualitative Screening and Activity Assay of L-asparaginase-Producing Fungi from Tempeh - Niva Tahyat; Yurnaliza; Liana Dwi Sri Hastuti (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to isolate and determine the types of fungi in tempeh that are capable of producing the enzyme L-asparaginase and how the enzyme activity is produced. The following steps were taken: Fungi were isolated using the pour plate method with Potato Dextrose Agar (PDA) medium; morphological characterization of fungi was performed macroscopically and microscopically.The ability to produce asparaginase was assessed qualitatively using modified liquid M9 medium and quantitative assay of L-asparaginase activity with the Nessler reagent. Potential fungi were identified based on identification books. The results of fungal isolation from tempeh yielded of 7 fungal isolates. Qualitative selection of fungal isolates from tempeh capable of producing L-asparaginase resulted in 4 fungi capable of producing the L-asparaginase enzyme, indicated by a pink color change in the medium. Quantitative assay was performed using an enzyme activity test .The results of quantitative selection showed that the highest activity of L-asparaginase enzyme was found in fungal isolate with the code TP 3, reaching 16,386 U/mL, which has been identified macroscopically and microscopically and is classified as belonging to the genus Aspergillus. These findings indicate that fungi from tempeh have the potential to produce the enzyme L-asparaginase.